Strategi Pemasaran Menggunakan Pendekatan Analisis SWOT pada PT Sumber Alam Unggul di Jombang - Mochamad Iqbal Assigaf; Lia Nirawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Sumber Alam Unggul is a company that sells organic agricultural products, such as organic fertilizers and pesticides. PT. Sumber Alam Unggul is the object of this research. The purpose of this study was to determine the marketing mix strategy in increasing sales at PT. Sumber Alam Unggul. The research method used is a qualitative descriptive method using the SWOT analysis method and data collection techniques through in-depth interviews, observation, documentation, and triangulation related to the marketing mix strategy which includes product, price, promotion, and place by researchers in identifying strengths, weaknesses, opportunities, and threats with the SWOT analysis method at PT. Sumber Alam Unggul. Based on this study, the results of IFAS and EFAS showed strengths with a score of 2,429 and weaknesses with a score of 1,098. While the EFAS results show opportunities with a score of 1.971 and threats with a score of 1.331. Based on the SWOT Analysis diagram, PT. Sumber Alam Unggul shows in Quadrant I by using an aggressive strategy that the company has opportunities and strengths so that it can take advantage of existing strengths and opportunities. the strategy that can be applied is to support the growth of an aggressive policy (Growth Oriented Strategy) to increase sales at PT. PT. Sumber Alam Unggul. Keywords: Marketing Strategy, SWOT Analysis, IE Matrix